Central American fathers’ perspectives on HPV vaccination: A qualitative study conducted in the United States - Denise Lima Nogueira; Denisse Delgado; Virginia Arango Moreno; Madelyne J. Valdez; Doris Lucero; Axel Hernandez Nieto; Nachalie Rodriguez-Cruz; Ana Cristina Lindsay (Global Public Health)
This qualitative study examined factors influencing Central American fathers’ views and behaviours on the HPV vaccine for their 11–17-year-old children, aiming to identify barriers and facilitators to vaccination in this underrepresented group. Semi-structured interviews were conducted with 23 fathers (mean age = 44.2, SD = 8.2) from El Salvador, Guatemala, and Honduras (91.3% foreign-born, average U.S. residency = 18.1 years). About 70% were married or living with a partner, and nearly half (47.8%) had less than a high school education. Most had one child aged 11–17, with 70% of children born in the U.S. Findings revealed gaps in fathers’ knowledge about HPV, its cancer-preventive benefits, and vaccine safety concerns. Cultural factors and gendered views on vaccination were prevalent. Around 33% of fathers reported that their children received an HPV vaccine recommendation, and all initiated vaccination. Fathers preferred receiving vaccine information from healthcare providers, highlighting their critical role in decision-making. Findings highlight the need for culturally tailored health promotion strategies aimed at Central American immigrant fathers. Public health campaigns should directly address vaccine safety concerns, incorporate cultural values, and emphasise the importance of informed decision-making, and engage healthcare providers to boost HPV vaccine uptake and reduce vaccine hesitancy in this population.